Differences in Parental Monitoring Components and Their Associated Health Indicators Between Sexual-Minority and Heterosexual Girls. Issue 3 (27th May 2017) - Montano, Gerald T.; McCauley, Heather L.; Miller, Elizabeth; Chisolm, Deena J.; Marshal, Michael P.
ABSTRACT: Our study sought to assess whether parental monitoring and their associations with health behaviors differed for heterosexual girls compared to sexual-minority girls (girls who identified as lesbian or bisexual, endorsed same-sex attraction, or had same-sex romantic or sexual partners). We analyzed three components of parental monitoring—adolescent disclosure, parental solicitation, and parental knowledge—between heterosexual and sexual-minority girls. We also tested if the associations between these three constructs and adolescent relationship abuse, suicidality, heavy drinking, binge drinking, anxiety symptoms, and depressive symptoms were different for heterosexual girls compared to sexual-minority girls. Sexual-minority girls were less likely to disclose accurately to their parents their location and activities and perceived their parents asked less and knew less about their location and activities than did heterosexual girls. Heterosexual girls who reported higher levels of adolescent disclosure were less likely than were sexual-minority girls to report suicidality and anxiety symptoms. Additionally, heterosexual girls who reported higher levels of parental knowledge were also less likely than were sexual-minority girls to report anxiety and depressive symptoms. These findings suggest that parental monitoring may not be as protective for sexual-minority girls as it is for heterosexual girls.